2010
DOI: 10.3382/ps.2009-00316
|View full text |Cite
|
Sign up to set email alerts
|

The effects of commercial cool water washing of shell eggs on Haugh unit, vitelline membrane strength, aerobic microorganisms, and fungi

Abstract: Current egg washing practices use wash water temperatures averaging 49 degrees C and have been found to increase internal egg temperature by 6.7 to 7.8 degrees C. These high temperatures create a more optimal environment for bacterial growth, including Salmonella Enteritidis if it is present. Salmonella Enteritidis is the most common human pathogen associated with shell eggs and egg products. Its growth is inhibited at temperatures of 7.2 degrees C and below. The objective of this study was to determine if com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 31 publications
1
13
0
Order By: Relevance
“…Albumen height and HU values tend to decrease (Figure 1) during storage, which concurs with the finding of others (Caudill et al, 2010;Musgrove, 2005).…”
Section: Methodssupporting
confidence: 79%
“…Albumen height and HU values tend to decrease (Figure 1) during storage, which concurs with the finding of others (Caudill et al, 2010;Musgrove, 2005).…”
Section: Methodssupporting
confidence: 79%
“…In fact, a treatment with cool water, maintained at a pH of 10 to 12, has the potential of reducing also the internal egg temperature during and after processing, enhancing the physical qualities of the eggs, and improving their microbial quality. Using different schemes of temperature, Caudill and others () obtained a reduction from 2.98 to 3.12 log CFU/mL.…”
Section: Postharvest Methods For Reducing the Risk Of Salmonellosis Dmentioning
confidence: 94%
“…Due to the concern that using a high temperature during egg washing may determine changes in egg quality, several studies have aimed to this point, evaluating as well the reduction of microbial load. Caudill and others () concluded that wash water temperature did not significantly affect average Haugh Unit values, albumen height, vitelline membrane strength or aerobic bacteria in the shell matrix, but did affect average numbers of aerobic microorganisms on the exterior shell surfaces. In fact, a treatment with cool water, maintained at a pH of 10 to 12, has the potential of reducing also the internal egg temperature during and after processing, enhancing the physical qualities of the eggs, and improving their microbial quality.…”
Section: Postharvest Methods For Reducing the Risk Of Salmonellosis Dmentioning
confidence: 99%
See 1 more Smart Citation
“…The vitelline membrane strength is an indication of internal quality of an egg. It surrounds the yolk and keeping it separated from the albumen, a strong vitelline membrane will prevent water diffusing from albumen into the yolk (Caudill et al, ). In this study, 20 and 100 IU/kg VE significantly increased the vitelline membrane strength compared with 0 IU/kg VE.…”
Section: Discussionmentioning
confidence: 99%